The association between adipokines and pulmonary diseases: a mendelian randomization study - Dongcai Wu; Ziyuan Wang; Keju Wang; Yuhan Wang; Tan Wang (BMC Pulmonary Medicine, 2024)
Abstract Background The role of adipokines in the development of lung diseases is significant, yet their specific relationship with different lung diseases remains unclear. Methods In our research, we analyzed genetic variations associated with adipokines and various lung conditions such as interstitial lung disease, chronic obstructive pulmonary disease, asthma, lung cancer, sleep apnea, pneumonia, and tuberculosis, using data from public genome-wide studies. We employed Mendelian randomization techniques, including inverse variance weighting, weighted median, and MR-Egger regression methods, and conducted sensitivity checks to validate our findings. Results A study using the FinnGen database, which included 198,955 participants, identified 13 SNPs associated with adiponectin. Notably, adiponectin was found to significantly reduce the risk of interstitial lung disease and idiopathic pulmonary fibrosis. However, little evidence was found to establish a direct cause-effect relationship between the six adipokines and several other lung conditions, including sarcoidosis, asthma, chronic obstructive pulmonary disease, lung cancer, tuberculosis, pneumonia, and sleep apnea syndrome. Conclusion This study reveals a reverse link between adiponectin levels and the likelihood of interstitial lung disease, including idiopathic pulmonary fibrosis.